2020
DOI: 10.31235/osf.io/rvqze
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cultivation of Social Work Knowledge: Towards a More Robust System of Peer Review

Abstract: In a recent issue of Families in Society, Caputo (2019) argues for the "centrality" of peer review in the cultivation of social work knowledge. Specifically, he favors the double-blind model of peer review. In this paper, I argue that social work should adopt a more dynamic set of reviewing practices. First, I define some terminology and discuss the limitations of the current double-blind model. Then, I describe recent trends in peer review, which I argue foster a more robust and open system. I frame this disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…This effort can be complemented by other types of methodological and professional reform such as the improvement of study conceptualization and design (Gelman, 2016;Wasserstein & Lazar, 2016) and strengthening of the peer-review system (Dunleavy, 2020). Journal editors, funders, and institutional leadership can encourage practical changes to the way we conduct, evaluate, report, and disseminate our research (Dunleavy, 2021(Dunleavy, , 2020Rothman, 1998;Shlonsky et al, 2002;Smaldino & McElreath, 2016). Researchers could be encouraged to routinely (1) engage in sample size planning;…”
Section: Alternative Approachesmentioning
confidence: 99%
“…This effort can be complemented by other types of methodological and professional reform such as the improvement of study conceptualization and design (Gelman, 2016;Wasserstein & Lazar, 2016) and strengthening of the peer-review system (Dunleavy, 2020). Journal editors, funders, and institutional leadership can encourage practical changes to the way we conduct, evaluate, report, and disseminate our research (Dunleavy, 2021(Dunleavy, , 2020Rothman, 1998;Shlonsky et al, 2002;Smaldino & McElreath, 2016). Researchers could be encouraged to routinely (1) engage in sample size planning;…”
Section: Alternative Approachesmentioning
confidence: 99%
“…Because of this variability and the broader technological and institutional changes occurring across scholarly publishing (see generally Tennant et al, 2017), scientific and philosophical evaluation must advance beyond the traditional institutions and norms used to assess journal quality. A framework is needed to capture how and why some journals review and publish what might be called genuine contributions to the corpus of knowledge more frequently than others -the latter of which varyingly publish (and thus perhaps tacitly endorse) false or ambiguous claims (Camerer et al, 2018;Dunleavy, 2021;Gambrill, 2018;Open Science Collaboration, 2015). This framework will need to account for both momentary states (i.e., how a journal functions at a given timepoint) and wider trends, which extend across years and decades.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in their literature search of grant peer review, Guthrie et al (2017) found relatively strong evidence for anti-innovation bias. journals may hinder the development of a robust body of knowledge (Dunleavy, 2021), by introducing false, misleading, unverified, or otherwise unjustified claims into the scholarly literature (Akça & Akbulut, 2021;Akerlof & Michaillat, 2019;Ioannidis, 2016;Smaldino & McElreath, 2016). The offshoot of these differences, however, is that journals can, in principle, be appraised and contrasted in accordance to how well they function in their role as gatekeepers.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this variability and the broader technological and institutional changes occurring across scholarly publishing (see generally Tennant et al, 2017), scientific and philosophical evaluation must advance beyond the traditional institutions and norms used to assess journal quality. A framework is needed to capture how and why some journals review and publish what might be called genuine contributions to the corpus of knowledge more frequently than othersthe latter of which may varyingly publish (and thus perhaps tacitly endorse) false or ambiguous claims (Camerer et al, 2018;Dunleavy, 2021;Gambrill, 2018;Open Science Collaboration, 2015). This framework will need to account for both momentary states (i.e., how a journal functions at a given timepoint) and wider trends, which extend across years and decades.…”
mentioning
confidence: 99%
“…9 For instance, the attempt to distinguish between predatory and non-predatory (or "good" and "bad") journals (Siler, 2020) resembles Popper's (1959Popper's ( /1968) classical formulation of the demarcation problem (i.e., how to distinguish science from pseudoscience). Contemporary questions about the role of journals and publishers in the development and growth of scholastic knowledge (see Dunleavy, 2021;Lock, 1985, especially Chapter 6) mirror investigations into the concept of, and theories about, scientific progress (e.g., Lakatos & Musgrave, 1970;Laudan, 1977). Finally, the self-governance of scholarly communities (including the reform of journal publication practices and standards; e.g., Dunleavy, 2020a;Hardwicke et al, 2020) have links to broader inquiries into the workings, policing, and self-correction of scientific communities (e.g., Kuhn, 1962;Merton, 1973;Zuckerman & Merton, 1971).…”
mentioning
confidence: 99%